Scientific and Methodological Foundations of Teaching Karakalpak Language and Literature in 8th-9th Uzbek Grades - Yusupova Aysulıw Konısbaevna (Scientific Trends, 2025)
Improving the scientific and methodological foundations of teaching karakalpak language and literature in uzbek grades 8-9is and the principles of compiling textbooks, improving methodological issues using problematic, review texts based on the materials presented in the karakalpak language and literature in uzbek grades 8-9is lesson program, lesson classes and teaching methods. He mechanism of using interactive methods in modern lessons has been improved; it has been strengthened by teacher motivation based on the needs of teachers, using effective problem-solving situations in teaching karakalpak language and literature in uzbek grades 8-9is and activating the communicative process.
Keywords: The process of the lesson, training, interactive technologies, literature, poetry, method, genres, publicistic, literary conference, activiry of the club, extra classes, character, creative work.